To travel or not to travel: 'Weather' is the question. Modelling the effect of local weather conditions on bus ridership. (January 2018) - Tao, Sui; Corcoran, Jonathan; Rowe, Francisco; Hickman, Mark
Highlights: (S)ARIMAX models were used to capture the hourly effects of weather on bus ridership. Both concurrent and lagged effects of weather on bus ridership were investigated. Bus ridership patterns vis-à-vis weather was captured at system, destination and stop levels. The response of bus usage to change in weather conditions was highly localised. Real-time weather information may be incorporated in the operation of bus transit. Abstract: While the influence of weather on public transport performance and ridership has been the topic for some research, the real-time response of transit usage to variations in weather conditions is yet to be fully understood. This paper redresses this gap by modelling the effect that local weather conditions exert on hourly bus ridership in sub-tropical Brisbane, Australia. Drawing on a transit smart card data set and detailed weather measurements, a suite of time-series regression models are computed to capture the concurrent and lagged effects that weather conditions exert on bus ridership. Our findings highlight that changes in particularly temperature and rainfall were found to induce significant hour-to-hour changes in bus ridership, with such effects varying markedly across both a 24 h period and the transit network. These results are important for public transport service operations in their capacity to inform timely responses to real-time changes in passengers' travel demand induced by the onset of particular weather conditions.